Pengembangan Budaya Islami Melalui Inovasi Pendirian Kampung Al-Quran di Ranting Muhammadiyah Sumbersari Kecamatan Ciparay Kabupaten Bandung - Iim Ibrohim; Hendar Riyadi; Muhtadin Muhtadin; Muhammad Idris; Taufik Rahman Saleh; Azkazzia Awliya Ahmad (Pusat Riset dan Inovasi Nasional, 2025)
The development of Islamic culture in local communities is an important foundation in the formation of a moral, productive and progressive community character. This research reports a community service program through the establishment of Al-Quran Village in Muhammadiyah Sumbersari Branch, Ciparay District, Bandung Regency. This program aims to build Al-Quran learning infrastructure, increase understanding and practice of Islamic values, and produce Quranic cadres who are active in da'wah. Implementation methods include coaching, cadre training, and routine halaqah activities. The results show an increase in community participation, the formation of a solid Quranic community, and an increase in religious understanding. The novelty of the program lies in the integration of education, da'wah, and community-based empowerment with the use of digital technology for sustainability.